The impact of the customs environment on Vietnam’s exports - Nguyen, Thanh Tuan; Luong, Tinh; Trinh, Thi Thu Huong; Nguyen, Gia Khuong; Dang, Thi Kim Thoa (Asian Economic and Financial Review, 2023)
This paper aims to study the impact of the customs environment on Vietnam’s exports, using panel data with 11 variables collected from 81 trading partners of Vietnam in the period between 2014 and 2019. The customs environment index (CEI) is determined by four component indexes: i) ease of cross-border trading, ii) prevalence of non-tariff barriers, iii) trade tariffs, and iv) corruption perception, with weights for each component calculated by the Analytic Hierarchy Process (AHP). The gravity model is employed and run using R software version 4.0.4. The results indicate that the customs environment has a significantly positive impact on Vietnam’s exports at the level of 1%; each percentage improvement in the CEI will lead to a 1.8105% increase in Vietnam’s exports (ceteris paribus). In other words, the convenience of the customs environment could promote Vietnam’s exports. By calculating the CEI of all countries, the results also show that the customs environment in Vietnam has improved during the investigated period, from 0.57 in 2014 to 0.59 in 2019, but this improvement is not considerable. When compared to Association of Southeast Asian Nations (ASEAN)-6 countries, Vietnam has a relatively modest customs environment record. These are critical findings for the implementation of necessary policies in Vietnam.